1999
DOI: 10.1300/j082v37n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Homophobia

Abstract: Medical student homophobia, if left unchallenged, will hinder care provided to homosexual patients. Physician homophobia may disallow a healthy doctor-patient relationship and may cause a decrease in patients' ability to disclose sensitive issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
1
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 14 publications
8
51
1
13
Order By: Relevance
“…Our results are in accordance with the literature that reports the strong influence of gender on attitudes towards homosexuality, with the male gender being consistently associated with more negative attitudes [27][28][29][30][31]33 both in traditional and modern forms of homophobia.…”
Section: Medical Students' Attitudes Towards Lesbians and Gay Mensupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in accordance with the literature that reports the strong influence of gender on attitudes towards homosexuality, with the male gender being consistently associated with more negative attitudes [27][28][29][30][31]33 both in traditional and modern forms of homophobia.…”
Section: Medical Students' Attitudes Towards Lesbians and Gay Mensupporting
confidence: 92%
“…36,37 These findings are in accordance with studies reporting that students with homosexual friends acquire more positive attitudes and may hold less stigmatizing attitudes even prior to the medical school. 29,30 In recent studies, the frequency of clinical encounters with LGBT patients showed as a predictor of less negative attitudinal scores 26,27 which was not verified in our study. Even so, it is important to highlight that in our sample the majority of students (60%) did not have any contact with patients that identified as LGB.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…However, available data from studies based on physician surveys suggest that many clinicians may have negative attitudes toward LGB individuals, which could affect clinicians' ability to provide appropriate care to this population. A study published in 1999 surveyed 100 medical students at a Midwestern U.S. medical school and found that 28% of respondents agreed with the statement "homosexuality is immoral" and 29% agreed that "homosexuality endangers the institution of the family" (46). Another study surveyed physicians from a medical society and academic center in a Southern California city in 1999 and reported a much smaller proportion of negative attitudes toward LGB individuals, but the response rate for this survey was only 13%, raising the possibility of a more biased sample than the 1999 Midwestern study of medical students (95).…”
Section: Health Care For Lgb Adolescentsmentioning
confidence: 99%
“…[24][25][26] Deficits in cultural competency among physicians and overt anti-SGM bias and discrimination contribute to the creation and maintenance of disparities. [27][28][29][30][31][32][33] Anti-SM bias has been well documented among medical trainees and providers, 15,34,35 whereas contact with SGM (before or during medical education) consistently predicts reduced anti-SGM bias, greater comfort and willingness to serve SGM patients, and greater willingness to work with SGM colleagues. 34,[36][37][38][39][40][41][42] Conversely, medical trainees with less contact with SM are more likely to express anti-SM attitudes.…”
Section: Discussionmentioning
confidence: 99%